Spin Polarized Electronic Transport and Photocurrent in Chiral Methionine Molecule via Magnetic Tunnel Junction Model from First Principles. Issue 9 (11th July 2022) - Xu, Yingdan; Han, Xuefei; Xiao, Yin; Wang, Yong; Mi, Wenbo
Abstract: The spin‐dependent transport properties through chiral amino acids and their modulations by light and magnetic field are important for understanding the intrinsic magnetism and photomagnetic coupling of chiral molecules. Here, the spin‐dependent electronic transport through chiral methionine (R, S‐MET) molecules is studied by theoretical calculations through a magnetic tunnel junction (MTJ) model. R‐MET molecule outputs fully spin polarized photocurrents with different spin channels, while S‐MET is insensitive under polarized light, revealing the spin polarized photocurrent selectivity of chiral molecules. Photocurrent increases greatly in Fe4 N/S‐MET/Au MTJ, where S‐MET shows unidirectional spin filtering effect. Fully spin polarized photocurrent appears in Fe4 N/R, S‐MET/Au MTJs, whose spin channel can be switched by adjusting magnetization directions. Particularly, chiral‐induced spin selectivity effect appears in Fe4 N/R, S‐MET/Au MTJs under specific polarized light and magnetization direction. Understanding the spin‐dependent electronic transport of chiral amino acids can provide a theoretical foundation for life science and bioelectronic devices. Abstract : This work reports the spin‐dependent transport properties through chiral methionine (R, S‐MET) molecules by first‐principles calculations via a magnetic tunnel junction model. The spin‐dependent photoelectronic and transport properties through amino acids are important for designing bioelectronic devices and understanding life science.